Research Progress of Therapeutic Enzymes and Their Derivatives: Based on Herbal Medicinal Products in Rheumatoid Arthritis - Cai, Ming; Ni, Wei-Jian; Han, Lan; Chen, Wei-Dong; Peng, Dai-Yin (Frontiers in Pharmacology, 2021)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disorder characterized by persistent synovitis, cartilage destruction, and joints deformities, which results in a wide range of disabilities, and increased mortality, thus imposing enormous burdens. Several drugs with immunomodulatory and anti-inflammatory properties are being used in the conventional (allopathic) system of medicine to treat RA. However, the long-term use of these drugs is associated with serious side effects due to its short poor bioavailability and biological half-life. These limitations greatly promote the research and application of newer drugs with low or no toxicity for the RA treatment. Meanwhile, a growing number of studies demonstrate that several herbs present certain anti-inflammatory and anti-arthritic activities through different enzymes and their derivatives, which indicate that it is a promising therapeutic strategy when targeting these mediators based on herbal medicinal products in RA research. In this review, we summarize the roles of the main enzymes and their derivatives in the RA pathogenesis, and clearly highlight the targeted action of herbal medicinal products that have anti-RA activity. Our review provides timely and critical reference for the scientific rationale use of herbal medicinal products, with the increasing basic research and clinical application of herbal medicinal products by patients with RA.